Genetic characterization and ancestry of the admixed population of Marajó Island, northern of Brazil, with autosomal and lineage markers. Issue 1 (December 2019) - Martins, S.; Simão, F.; Pinheiro, L.M.L.; Nguidi, M.; Deccache, L.; Gusmão, L.; Carvalho, E.F.
Abstract: To investigate the genetic background of the Marajó population, samples from unrelated individuals were selected, with matrilineal or patrilineal local ancestry for at least three generations. A total of 72 male samples were genotyped for 27 Y-STRs, 65 for 46 AIMs and 55 were sequenced for the mtDNA control region. Low haplotype diversities were obtained for Y-STRs and mtDNA, when compared to other Brazilian admixed populations, most probably due to the small size of the population and the geographic isolation of the island. Based on HVI, significant genetic distances were found between Marajó and Brazilian populations from the North, Northeast, South and Southeast regions. For mtDNA, Native American haplogroups were the most prevalent, followed by the African and European haplogroups. For the autosomal markers, a 40.7% European ancestry was found, followed by 33.2% of Native American and 26.1% of African contributions.